Community and Individual in Classical Democracy. Nature, Law and Society (Circe de clásicos y modernos, 2018)
Nowadays, the vast majority of scholars agree that in the Greek democracy there was never something analogous to the modern concept of human rights. This essay examines whether classical democracy was, as in the Modern Age, preceded or accompanied by the development of the notion of natural law, common to all mankind and based on dignity’s natural equality among individuals. The pages that follow investigate texts by some VI-V B.C. philosophers and theoreticians that either show some evidence of an account of human progress or an outline of the hypothetical idea of the social contract, or that analysed the political development on the basis of the νόμος-φύσις anthithesis. It’s impossible to find the existence of individual guarantees in Athenian democracy previous and above the power of the δῆμος and, in the same way, there existed no Greek liberal thought that could have served as basis for that legal definition.
Keywords: natural law; progress; social contract; nomos; physis